Digital Platforms to Support Feeding, Physical Activity and Training by Cerebral Palsy - Hamburg, Ileana; Lütgen, Gabriela (Archives of Business Research, 2018)
Cerebral palsy (CP) is one of the most common motor disability in rehabilitation, has antenatal antecedents and is often multi-factorial. Many people with CP are physically inactive, have difficulties with eating and drinking. The authors work together with organisations of people with disabilities, particularly people with CP to find solutions for improving Quality of Life (QoL) of these people. Within the Erasmus+ project CP-WELLBEING the problems are connected with inclusive nutrition, physical activities and training by using interactive ICT platforms. The methods used in the project and the description of the developed training materials are presented in part 5 of this paper.